Bioremediation of PAHs and heavy metals co-contaminated soils: Challenges and enhancement strategies. (15th February 2022) - Ali, Mukhtiar; Song, Xin; Ding, Da; Wang, Qing; Zhang, Zhuanxia; Tang, Zhiwen
Abstract: Systemic studies on the bioremediation of co-contaminated PAHs and heavy metals are lacking, and this paper provides an in-depth review on the topic. The released sources and transport of co-contaminated PAHs and heavy metals, including their co-occurrence through formation of cation-π interactions and their adsorption in soil are examined. Moreover, it is investigated that co-contamination of PAHs and heavy metals can drive a synergistic positive influence on bioremediation through enhanced secretion of extracellular polymeric substances (EPSs), production of biosynthetic genes, organic acid and enzymatic proliferation. However, PAHs molecular structure, PAHs-heavy metals bioavailability and their interactive cytotoxic effects on microorganisms can exert a challenging influence on the bioremediation under co-contaminated conditions. The fluctuations in bioavailability for microorganisms are associated with soil properties, chemical coordinative interactions, and biological activities under the co-contaminated PAHs-heavy metals conditions. The interactive cytotoxicity caused by the emergence of co-contaminants includes microbial cell disruption, denaturation of DNA and protein structure, and deregulation of antioxidant biological molecules. Finally, this paper presents the emerging strategies to overcome the bioavailability problems and recommends the use of biostimulation and bioaugmentation along with the microbial immobilization for enhanced bioremediation of PAHs-heavy metals co-contaminated sites. Better knowledge of the bioremediation potential is imperative to improve the use of these approaches for the sustainable and cost-effective remediation of PAHs and heavy metals co-contamination in the near future. Graphical abstract: Image 1 Highlights: PAHs and heavy metals co-occur in soil via the cation-π interaction. Metal stress positively enhances EPSs, genes, enzyme and organic acid production. A major challenge for bioremediation is reduced co-contaminants bioavailability. Co-contamination initiates synergistic cytotoxicity and molecular deregulation. Strategies for enhanced bioremediation of co-contaminants are proposed.